A Student's Atlas of Flowering Plants: Some Dicotyledons of Eastern North America - Wood C. E. (New York Evanston San Francisco London Harper&Row, 1974)
Detailed drawings of the biology systems of one hundred twenty selected flowering dicotyledons are presented with descriptive terms and modes of pollination and seed dispersal.
Keywords: 58